SEMIOTIKA TANDA VERBAL DAN VISUAL PADA IKLAN KAMPANYE PENCEGAHAN PENYEBARAN COVID-19 - Putri I Gusti Ayu Vina Widiadnya (Universitas Warmadewa, 2020)
This research was conducted to determine the types of signs and the meaning behind the series of signs that appear in advertisements, so it can be seen whether the advertisement has used signs that can change people's views or not. The data was taken from the Public Service advertisement about the campaign to prevent Covid-19 spread. Data in the form of brochures, images, posters, billboards, and download advertisements from the website were used in this research. The analytical method used was verbal and visual communication semiotics. The collected data were analyzed qualitatively based on the theory from Barthes (1967). In visual signs, the data were analyzed based on the theory proposed by Wierzbicka (1996) to analyze the colors that appear in the signs presented. Based on the analysis of the data, there are three findings which are the results of this study: first, verbal signs that appear in every advertisement, contain connotation and denotation meaning. Second, the visual signs that appear show a number of images that have various meanings in accordance with the context behind the advertisement, even through ads that do not contain verbal signs can provide meaningful messages to the reader. Third, verbal signs and visual signs in addition to being able to support and interpret each other, these two signs can stand alone and show their own meaning of the message to be conveyed to the reader.